Processing and luminescence of Eu/Dy-doped Sr2MgSi2O7 glass-ceramics. Issue 1 (January 2021) - Fernández-Rodríguez, L.; Levy, D.; Zayat, M.; Jiménez, J.; Mather, G.C.; Durán, A.; Pascual, M.J.
Abstract: Glass-ceramics based on the Eu/Dy-doped Sr2 MgSi2 O7 phosphor have been obtained from sintering and crystallization of glass powders. Electric and gas furnaces were employed for glass melting. The doped parent glasses show red emission under excitation of UV light whereas the corresponding glass-ceramics show blue emission. The microstructure of the glass-ceramics and the crystals responsible for the blue emission were observed by scanning electron microscopy-cathodoluminescence. The composition of the crystallised phases and the distribution and incorporation of rare-earth (RE) ions into the crystals and remaining glassy phase were determined by X-ray diffraction and energy dispersive X-ray analysis, respectively. Photoluminescence emission spectra showed a main peak at 484 nm assigned to the typical Eu 2+ transitions under excitation at 390 nm in the glass-ceramics. The presence of Dy 3+ improved persistence in the samples melted in the gas furnace. The glass-ceramics are sensitive to temperature, which modifies both the persistence time and red-blue luminescence.